International Trading Prices Of India’s Oilseed Crops: Growth Rates, Elasticities And Foreign Trade Policy - M.B. Dastagiri; S.M Jainuddin (European Scientific Journal, ESJ, 2017)
World prices influence international trade and so economic precision is required. This foreign trade research study examines exports and imports of India’s major oilseeds from 1990-91 to 2015-16. The methodology employed is the estimation of CAGR, Instability Index, Export import price elasticities of oilseeds and identification of top export import destinations. The results show that export prices of groundnut, soybean, niger, safflower, sesamum and sunflower were higher than import prices indicating that India has a comparative advantage in these crops. The terms of trade of India’s oilseeds were found to have increased for all oilseeds except mustard crop. The exports price growth rate of groundnut, niger, safflower and sunflower were higher than imports. The study found that among oilseeds, mustard (0.97 %) has high export elasticity and that export imports prices of groundnut, soybean, safflower, sunflower and niger crops were found to be stable. It also found that India’s major exports destinations for groundnut, soybean, niger seeds, sesamum, and sunflower are Indonesia, USA, South Korea and Philippines respectively, whereas major imports destinations are Germany, USA, Nigeria and Ukraine for groundnut, soybean, sesamum, and sunflower respectively. The study suggests that multilateral trade relationship with countries having high export imports share would help in smooth trade of oilseeds. These findings have important implications for policy research and R&D strategies in response and re-orientation of the R&D system to the changing trade scenario to benefit from WTO.